Influence of socio-family variables on parental assessment of the pragmatic development of children under 4 years of age - Botana, Iria; Peralbo, Manuel (Frontiers in Psychology, 2024)
Introduction: Interest in pragmatic development and its assessment has increased in recent years, not only because of the predictive value of pragmatic impairments as warning signs in the detection of multiple developmental disorders, but also because of the consideration that pragmatics has received in the field of mental disorders. Current contexts of child development assessment require pragmatic assessment instruments that accurately define profiles and take into account the immediate context in which they develop. Parents' knowledge of their children's abilities is supported by exhaustive observation over time of regularities in their behavior. But it is true that the way a caregiver interprets behavior is mediated by multiple variables. The aim of the present study, therefore, is to shed light on the possible influence of parental belief systems on the assessment of children's pragmatic development by analyzing the relationship between sociofamilial variables and the assessment of pragmatic competence.Method: A total of 215 educational centers across Spain participated in the study. The final sample was of 262 parents of boys and girls between 6 and 48 months of age.The parental questionnaire for the evaluation of pragmatic development, The Pragmatics Profile, in an adapted Spanish version, was applied along with a number of items for the evaluation of parental beliefs.Results: Analyses confirm the existence of an effect of child development conceptions and other socio-familial variables on the assessment of pragmatic development between 6 and 48 months of age. Furthermore, the results indicate that better scores on pragmatic development are associated with parents with higher socioeconomic and educational levels, greater number of children and more interactionist conceptions and realistic.The effect of parental conceptions on the evaluation of pragmatics points to the need to obtain convergent measures in an area as complex as that of communicative development in early childhood, especially taking into account that an evaluation which is neutral and free from context is not possible or indeed desirable. Pragmatic development must be evaluated within this contextual framework and should take into account each of the variables present therein. Hence the complementarity between parental reports and performance-based test.